IMPORTANCE OF OBSERVATION AND INTERVIEW METHODS AS DATA COLLECTION TOOLS IN THE OIL & GAS SECTOR: A STUDY ON ERGONOMICS AND SAFETY CULTURE - Oke, Rohit; Phadke, Supriya; Kulkarni, Milind A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
One of the top ten countries in the world for oil production is the United Arab Emirates (UAE). Abu Dhabi, the sixth-largest oil producer in the world, is home to about 96% of the nation's estimated 100 billion barrels of proven oil reserves. On average, the United Arab Emirates produces 3.2 million barrels of petroleum and liquids every day. This study highlights the use of observation and interview techniques as efficient data gathering methods in the oil and gas industry, with a focus on the relationship between ergonomics and corporate safety culture. Operators, supervisors, safety officials, technicians, and occupational health specialists made up the study's sample population. Results show that, in contrast to conventional questionnaire approaches, observation and interview techniques offer deeper insights into workplace habits and practices. These techniques enable in-the-moment evaluations and sophisticated comprehension, which are essential for improving safety and ergonomic procedures. The outcomes show how effective they are at spotting important safety issues and providing useful advice.